Analisis Soal Ujian Nasional Tahun 2013/2014 Menggunakan Digital Mark Reader (DMR) Di SMP Negeri 1 Tanon - Praeska, Febrianto Wahyu Dwi, Prof. Dr. Budi Murtiyasa, M.Kom, Dr. Ahmad Muhibbin, M.Si (2015)
This research aims to: 1. Knowing the ability of DMR in analysis of difficulty level, discrimination power, and distractor functions of the National Exam Questions, 2. Knowing the assurance level of the difficulty analysis results of National Exam Questions by DMR compared to manual calculation, 3. Knowing analysis results of difficulty level, discrimination power, and distractor functions of the National Exam Questions and improvements to be made. Type of this research is qualitative research with the development of conceptual models. Analysis of the data used in this research is content analysis. Procedure development starting from product development, product testing and products assessment. Data was collected by questionnaire in the form of the National Exam Questions. The results of this research are: 1. Difficulty level analysis of Indonesian Questions in the enough or moderate category, English in the too difficult and enough or moderate category, Science in the too difficult and enough or moderate category, Mathematics in the category of too difficult and enough or moderate. 2) Difficulty level of National Exam Questions being analyzed with DMR or manually, showed no significant difference at all the National Exam Questions being tested. That is the difficulty analysis of questions, the teacher can perform difficulty analysis of questions using DMR. 3) Follow up difficulty level analysis result of of National Exam Questions that can be done for an easy category is by removing the item and are not issued anymore, while the difficult category, questions items subject to reexamination, tracked, and traced so it can be known a factor that causes the items in question difficult to answer by students, whether the questions sentence is less clear, whether instructions on how to do the questions is difficult to understand, or whether the question is there are terms that are not clear, and after repair, the items are removed again in the the next achievement test.